Investigation of the spectrum for Sturm–Liouville problems with a nonlocal boundary condition - Skučaitė-Bingelė, Kristina; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2013)
In this paper, we analyze the Sturm–Liouville problem with one classical first type boundary condition and the other Samarskii–Bitsadze type nonlocal boundary condition. We investigate how the spectrum of this problem depends on the parameters γ and ξ  of the nonlocal boundary condition. Some new results are given as graphs of the characteristic function.
Keywords: two-point Nonlocal Boundary Condition; Sturm–Liouville problem,; complex eigenvalues